Application of Internet of Things in the Field of Staple Food Commodity Agriculture: Literature Review - Khofida, Nisa; M. Syauqi Haris; Mochammad Anshori (Program Studi Teknik Informatika Universitas Nusa Putra, 2025)
Kebutuhan akan pertanian yang efisien, produktif, dan berkelanjutan di Indonesia menuntut penerapan teknologi modern. Salah satu teknologi The need for efficient, productive, and sustainable agriculture in Indonesia demands the application of modern technology. One technology that offers significant solutions is the Internet of Things (IoT). This study presents a systematic literature review on the application of IoT to staple food commodity agriculture in Indonesia, with a focus on the use of soil sensors, automatic irrigation systems, and real-time data integration. The Systematic Literature Review (SLR) method was used to analyze 44 selected articles published between 2019 and 2024. The results of the study show that IoT technology contributes greatly to increasing water use efficiency, reducing operational costs, and increasing crop yields. In addition, the integration of this technology also has positive implications for the social and economic aspects of local agriculture. This study aims to provide an in-depth understanding of technology trends and development methods used, as well as identifying implementation challenges in the field. These findings are expected to be an important reference for academics, practitioners, and policy makers in formulating IoT-based agricultural development strategies in the future.